Patterns of recurrence in early‐stage oesophageal cancer after chemoradiotherapy and surgery compared with surgery alone. Issue 1 (29th October 2015) - Robb, W. B.; Messager, M.; Dahan, L.; Mornex, F.; Maillard, E.; D'Journo, X. B.; Triboulet, J.‐P.; Bedenne, L.; Seitz, J.‐F.; Mariette, C.; ,
Abstract : Background: Patterns of disease recurrence in patients with oesophageal cancer following treatment with neoadjuvant chemoradiotherapy and surgery (nCRTS) or surgery alone are poorly reported. An understanding of patterns of disease recurrence is important for subsequent treatment planning. Methods: An analysis was undertaken of patterns of disease recurrence from a phase III multicentre randomized trial (FFCD9901) comparing nCRTS with surgery alone in patients with stage I and II oesophageal cancer. Results: Some 170 patients undergoing surgical resection were included in the study. R0 resection rates were similar in the two groups: 94 per cent following nCRTS versus 92 per cent after surgery alone ( P  = 0·749). After a median follow‐up of 94·2 months, recurrent disease was found in 39·4 per cent of the overall cohort (31 per cent after nCRTS versus 47 per cent following surgery alone; P  = 0·030). Locoregional recurrence was diagnosed in 41 patients (17 versus 30 per cent respectively; P  = 0·047) and distant metastatic recurrence in 47 (23 versus 31 per cent respectively; P  = 0·244). Metastatic recurrence was more frequent in patients with adenocarcinoma than in those with squamous cell cancer (40 versus 23·1 per cent respectively; P  = 0·032). ypT0 N0 category was associated with prolonged time to mixed locoregional and metastatic recurrence ( P  = 0·009), and time to locoregional ( P  = 0·044) and metastatic ( P  = 0·055) recurrence. In multivariable analysis, node‐positive disease predicted both locoregional ( P  = 0·001) and metastatic ( P  < 0·001) recurrence. Conclusion: Locoregional disease control following nCRTS indicated a local field effect not related solely to completeness of resection. pN+ disease was strongly predictive of time to locoregional and metastatic disease recurrence. Abstract : Multimodal treatment reduces locoregional but not distant metastatic recurrence